Filsafat Pendidikan dan Penguatan Berpikir Logis dalam Pembelajaran Matematika di Era Globalisas - Naufal Ubaidillah, Muhamad; Rosyida, Diyana; Fa'izatul Fuadah, Lia; Muhlisin, Muhlisin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines how educational philosophy serves as a conceptual foundation for developing students' logical thinking abilities in mathematics learning amid globalization. The research employed a library-based method with a qualitative descriptive approach. Data were gathered from a synthesis of scientific journals, academic books, and educational reports published from 2020 to 2025, and were analyzed through data selection, thematic grouping, and conclusion drawing. The findings show that educational philosophy, especially constructivism, underpins student-centered mathematics learning that nurtures logical, critical, and structured thinking. Additionally, digital tools such as GeoGebra, Virtual Reality (VR), and interactive learning platforms prove helpful in clarifying abstract mathematical concepts. The study further reveals that the success of philosophy-based mathematics instruction depends largely on teachers' pedagogical skills, digital infrastructure readiness, and students' responsible use of technology. Accordingly, reinforcing philosophical grounding and digital literacy is urgently needed to address contemporary challenges in mathematics education.